2021
DOI: 10.1155/2021/5564040
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Validation of a Prognostic Model Based on Three Autophagy-Related Genes in Hepatocellular Carcinoma

Abstract: Background. Accumulating studies have demonstrated that autophagy plays an important role in hepatocellular carcinoma (HCC). We aimed to construct a prognostic model based on autophagy-related genes (ARGs) to predict the survival of HCC patients. Methods. Differentially expressed ARGs were identified based on the expression data from The Cancer Genome Atlas and ARGs of the Human Autophagy Database. Univariate Cox regression analysis was used to identify the prognosis-related ARGs. Multivariate Cox regression a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…BIRC5 expression could reflect aggressive histological and clinical behavior of HCC, correlating with poorer OS (Kapiris et al, 2019). Present studies have shown that BIRC5 is closely related with autophagy, and several survival indexes containing BIRC5 were proved to have promising predictive value (Yang et al, 2020;Qin et al, 2021;Wang et al, 2021). Jiao et al once reported that YAP promoted sorafenib resistance in HCC by upregulating BIRC5 (Sun et al, 2021).…”
Section: Discussionmentioning
confidence: 92%
“…BIRC5 expression could reflect aggressive histological and clinical behavior of HCC, correlating with poorer OS (Kapiris et al, 2019). Present studies have shown that BIRC5 is closely related with autophagy, and several survival indexes containing BIRC5 were proved to have promising predictive value (Yang et al, 2020;Qin et al, 2021;Wang et al, 2021). Jiao et al once reported that YAP promoted sorafenib resistance in HCC by upregulating BIRC5 (Sun et al, 2021).…”
Section: Discussionmentioning
confidence: 92%
“…We sought to examine the predictive value of ARGs that could be used to predict the prognosis of HCC patients. Qin et al constructed a prognostic model of ARGs for LIHC with partial data sets from TCGA (n=235) ( 36 ). However, to build the model in this study, we used the whole TCGA data set (n=346).…”
Section: Discussionmentioning
confidence: 99%